IMPLEMENTASI KEGIATAN INFAQ DAN SEDEKAH DALAM MEMBENTUK KARAKTER PEDULI SOSIAL SANTRI DI PONDOK PESANTREN AL-BAROKAH TLOGOMAS LOWOKWARU MALANG - Siti Fatimah; Rosichin Mansur; Adi Sudrajat (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
Aspects of life that help each other can create harmonious relationships among human beings. Moreover, in the realm of education, infaq and alms can be useful to shape the social care character of students in helping and respecting each other with people who are more in need. The purpose of this research is to find out the process of collecting, distributing, and implementing the Infaq and Alms Activities in Forming the Character of Social Care for Santri at the Al-Barokah Islamic Boarding School Tlogomas Lowokaru Malang. Researchers conducted research using descriptive qualitative methods on all students who participated in infaq and alms activities at the Al-Barokah Tlogomas Islamic Boarding School Lowokwaru Malang, amounting to 110 students. Data analysis was carried out by reduction data, presentation data, and conclusion drawing. The results of the research show that infaq and alms are structured and unstructured. As for structured activities, withdrawals are held every two weeks, while unstructured activities are carried out when there are sudden things about students and guardians of students and donations for victims of natural disasters. Kata Kunci: Infaq dan Sedekah, Karakter, Peduli Sosial